Covid-19 Mortality in an Acute Care Hospital: Association of Patient Factors With Decision to Forego the Intensive Care Unit. (April 2022) - Meisenberg, Barry R.; Qureshi, Sadaf; Somasekar, Monika Thandalam; Ali, Qurat; Karpman, Mitchell; Rhule, Jane
Background: Public awareness of the large mortality toll of COVID-19 particularly among elderly and frail persons is high. This public awareness represents an enhanced opportunity for early and urgent goals-of-care discussions to reduce medically ineffective care. Objective: To assess the end-of-life experiences of hospitalized patients dying of COVID-19 with respect to identifying the clinical factors associated with utilization or non-utilization of the ICU. Methods: Retrospective cohort study of hospital outcomes using electronic medical records and individual chart review from March 15, 2020 to October 15, 2020 of every patient with a COVID-19 diagnosis who died or was admitted to hospice while hospitalized. Logistic regression multivariate analysis was used to identify the clinical and demographic factors associated with non-utilization of the ICU. Results: 133/749 (18%) of hospitalized COVID-19 patients died or were admitted to hospice as a result of COVID-19. Of the 133, 66 (49.6%) had no ICU utilization. In multivariate analysis, the significant patient factors associated with non-ICU utilization were increasing age, normal body mass index, and the presence of an advanced directive calling for limited life sustaining therapies. Race and residence at time of admission (home vs. facility) were significant only in the unadjusted analyses but not in adjusted. Gender was not significant in either form of analyses. Conclusion: Goals of care discussions performed by an augmented palliative care team and other bedside clinicians had renewed urgency during COVID-19. Large percentages of patients and surrogates, perhaps motivated by public awareness of poor outcomes, opted not to utilize the ICU.